Eisrand und Karstpoljen am Westrand der Lukavicahochfläche (Westmontenegro) - Liedtke, Herbert (ERDKUNDE, 1962)
Observations on the Pleistocene ice margin of the Lukavica Highplateau northeast of Niksic (Montenegro), which was glacier covered during the cold phases of the Ice Age, show that the relief features of the exposed limestone decisively determined the course and altitude of the ice margin. The contrast between the formerly ice covered surfaces nearly free of glacial drift and the great accumulation of glacial drift in the courses of the terminal moraines is very striking. The channels of the melt water courses of the glacial phases may be traced by means of glacio-fluvial gravels. The smaller poljes with hydrographically rather ineffective swallow holes (ponors) were filled up during the cold phases so that eventually during a cold phase a complete surface drainage resulted; this was, however, unable to arrive at an even gradient. These meltwater courses of the cold phases terminated in large poljes where, because of their size, the swallow holes had not become blocked. The late- and postglacial re opening of the small ponors resulted - partly still under periglacial conditions - in a dissection of the glacial accumulations and thus interrupted the previously continuous channels.